The Routledge Companion to Free Will - Griffith, Meghan; Levy, Neil; Timpe, Kevin (Taylor & Francis, 2017)
Questions concerning free will are intertwined with issues in almost every area of philosophy, from metaphysics to philosophy of mind to moral philosophy, and are also informed by work in different areas of science (principally physics, neuroscience and social psychology). Free will is also a perennial concern of serious thinkers in theology and in non-western traditions. Because free will can be approached from so many different perspectives and has implications for so many debates, a comprehensive survey needs to encompass an enormous range of approaches. This book is the first to draw together leading experts on every aspect of free will, from those who are central to the current philosophical debates, to non-western perspectives, to scientific contributions and to those who know the rich history of the subject. Its 61 chapters, commissioned especially for this volume from the world's leading researchers, are framed by a General Introduction and briefer introductions for each of the six sections. A list of References, an annotated Suggested Reading list, and a short list of Related Topics are included at the end of each chapter.